Cultural diversity in international law : the effectiveness of the UNESCO convention on the protection and promotion of the diversity of cultural expressions - Richieri Hanania, Lilian (Milton Park, Abingdon, Oxon : Routledge, 2014)
'The UNESCO Convention on the Protection and Promotion of the Diversity of Cultural Expressions (CDCE) was adopted in 2005 and designed to allow States to protect and promote cultural policies. This book examines the effectiveness of the CDCE and offers ways by which its implementation may be improved to better attain its objectives. The book provides insight in how the normative character of the CDCE may be strengthened through implementation and increasingly recurrent practice based on its provisions. Hailing from various fields of international law, political and social sciences, the book's contributors work to promote discussions on the practical and legal influence of the CDCE, and to identify opportunities and recommendations for a more effective application. Part One of the book assesses the effectiveness of the CDCE in influencing other areas of international law and the work conducted by other intergovernmental organizations through the recognition of the double nature (cultural and economic) of cultural goods and services. Part Two focuses on the practice of the CDCE beyond the recognition of the specificity of cultural goods and services in international law by addressing the CDCE's call for greater international cooperation and stronger integration of cultural concerns in development strategies at the national and regional levels. The book will be of great use and interest to academics and practitioners in law, social and political sciences, agents of governmental and international organizations, and cultural sector stakeholders'--
The legal nature of the CDCE operational guidelines and their influence on the CDCE effectiveness / Anne-Thida Norodom -- Cultural development and technical and financial assistance on the basis of the CDCE / Antonios Vlassis -- The power of knowledge and transparency : networked opportunities in cultural policies and governance / Christine M. Merkel -- Implementing the CDCE in cultural relations and diplomacy : the mediterranean example / Karsten Xuereb -- EU protocols on cultural cooperation : an attempt to promote and implement the CDCE within the framework of bilateral trade negotiations / Catherine Soury-Desrosier -- The CDCE in the European Union : a mixed agreement and its judicial application / Magdalena Lickova -- Implementing the CDCE at the national and regional levels : the example of Brazil / Paula Wojcikiewicz Almeida -- Private sector contributions to the implementation of the CDCE in Brazil / Piata Stoklos Kignel -- Integrating culture in sustainable development : Quebec's agenda 21, a model for the implementation of article 13 / Veronique Guevremont -- The CDCE and the new education acts in Latin America / Laura Giannecchini -- General conclusions and recommedations / Lilian Richieri Hanania.
Includes bibliographical references and index.
Keywords: Convention on the Protection and Promotion of the Diversity of Cultural Expressions -- (2005); Multiculturalism -- Law and legislation; Cultural policy; Culture and law; Foreign trade regulation